Obstetric and neonatal outcome in pregnancies complicated by hemolysis elevated liver enzymes low platelet count syndrome at a tertiary care centre in India - Bang, Nidhi O.; Satia, Meena N.; Poonia, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The hemolysis elevated liver enzymes low platelet count (HELLP) syndrome is a serious complication in pregnancy characterized by hemolysis, elevated liver enzymes and low platelet count occurring in 0.4 to 0.7% of all pregnancies and in 10-12% of cases with severe preeclampsia. This present study will throw some light on occurrence, diagnosis, complications, treatment, mode of delivery and the neonatal outcome. Methods: A prospective observational study was conducted in the department of Obstetrics and Gynecology at Seth G.S. Medical College and KEM hospital which is a tertiary care centre in Mumbai in the state of Maharashtra India from September 2013 to December 2014 after the approval of institutional ethics committee. The inclusion criteria were only those patients in whom HELLP syndrome was diagnosed on the basis of blood investigations, laboratory parameters and clinical picture. All those patients who did not fulfill the diagnostic criteria for HELLP syndrome were excluded. Results: In our study, according to the Mississippi classification, 15% belonged to class 1, 62% to class 2 and 23% to class 3. The peak age of incidence was 21-30 years (78%) and majority were primigravida (57%). Majority (91%) presented with headache and the other associated complains were epigastric pain, nausea, vomiting and blurring of vision. Only 32% patients presented at term (>37 weeks), 65% patients were at 28-36 weeks of gestation and 3% had very early onset HELLP syndrome. Majority (65%) had severe hypertension (BP>160/110 mm of Hg) with albuminuria of grade +3 to +4. Majority (83%) of the patients were given injection MgSO4 either for prophylaxis or treatment of eclampsia. 65% patients delivered vaginally. 70% were live births, out of which 8% died in the early neonatal period. Severe maternal complications such as eclampsia, hematuria, acute kidney injury, abruption placentae, severe anemia and DIC were seen in 63% patients. 57% of patients were transfused with blood and blood products and 7% required intensive care management. Conclusions: A multidisciplinary approach is of utmost importance along with early diagnosis and prompt treatment to prevent the cataclysmic deterioration of patients with HELLP syndrome.